A flexible and skin-mountable elastic fiber-based sensor patch for healthcare monitoring. (27th May 2019) - Zang, Siyao; Wang, Qi; Wan, Jiaxin; Huang, Xinan; Ren, Xiaomin
Abstract: In this paper, we propose a flexible and skin-mountable elastic fiber-based sensor patch, enabling the detection of subtle human activities and physiological signals for personal healthcare. As the sensing component, the resistive type elastic fiber-based strain sensor is fabricated with the reduced graphene oxide coated elastic fiber, presenting great flexibility, stretchability, linearity, sensitivity, and responsivity. When the sensor patch was attached onto the surface of skin, the delicate deformation of the epidermis and muscles during subtle human motion was effectively detected. Through further waveform analysis, we acquired the personal healthcare information related to chewing degree, swallowing condition, pronouncing intention, respiration rate, cardiovascular stiffness, muscle strength, and central nervous system. Consequently, we provide a facile and reliable method for healthcare monitoring, showing great application prospect in caregiving and healthcare network.